Hydrogen adsorption on palladium anchored defected graphene with B-doping: A theoretical study. (19th February 2015) - Zhou, Qingxiao; Wang, Chaoyang; Fu, Zhibing; Yuan, Lei; Yang, Xi; Tang, Yongjian; Zhang, Hong
Abstract The effect of a combination of B-doping and vacancy-defect on the atomic adsorption of hydrogen on Pd-decorated graphene have been investigated using density functional theory simulations. The introducing of defect and B-dopant enhanced the adsorption of hydrogen molecule and the PDOS results indicated that the enhancement was contributed by the hybridization of B and H atoms. Furthermore, the adsorption of hydrogen molecule on Pd-decorated double-vacancy (DV) defective graphene lead to dissociated and chemisorbed states with the two separated H atoms bonding to the C atoms at vacancy sites. Interestingly, the B-doping decreased the interaction between the Pd-adatom and the defected graphene but increased the stability of the adsorption of dissociated H2. The activated states of H2 molecule occurred in the adsorption on single-vacancy (SV) defected graphene with stretched H–H bonds. Our results provide a potential approach for the engineering of graphene for hydrogen storage applications.